Reward Sharpens Orientation Coding Independently of Attention - Baldassi, Stefano; Simoncini, Claudio (Frontiers in Neuroscience, 2011)
It has long been known that rewarding improves performance. However it is unclear whether this is due to high level modulations in the output modules of associated neural systems or due to low level mechanisms favoring more 'generous' inputs? Some recent studies suggest that primary sensory areas, including V1 and A1, may form part of the circuitry of reward-based modulations, but there is no data indicating whether reward can be dissociated from attention or cross-trial forms of perceptual learning. Here we address this issue with a psychophysical dual task, to control attention, while perceptual performance on oriented targets associated with different levels of reward is assessed by measuring both orientation discrimination thresholds and behavioral tuning functions for tilt values near threshold. We found that reward, at any rate, improved performance. However, higher reward rates showed an improvement of orientation discrimination thresholds by about 50% across conditions and sharpened behavioral tuning functions. Data were unaffected by changing the attentional load and by dissociating the feature of the reward cue from the task-relevant feature. These results suggest that reward may act within the span of a single trial independently of attention by modulating the activity of early sensory stages through a improvement of the signal-to-noise ratio of task-relevant channels.